Employment and productivity growth in Tanzania's service sector - Mia Ellis; Margaret Stokes McMillan; Jed Silver (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Despite Tanzania's rapid recent growth, the vast majority of employment creation has been in informal services. This paper addresses the role that different subsectors of formal and informal services have played in Tanzania's growth. It finds that subsectors such as trade services contribute significantly to employment despite their relatively low productivity, while subsectors such as business and transportation services display higher productivity and improve the environment for other firms to operate. The paper also acknowledges the role of high-performing small and medium-sized service firms and the tourism sector in contributing further to Tanzania's growth and structural change.
Keywords: E26; L80; L83; O14; O17; 330; services; informal sector; economic growth; structural change; Tanzania; tourism